2018
DOI: 10.5395/rde.2018.43.e13
|View full text |Cite
|
Sign up to set email alerts
|

Management of dental erosion induced by gastro-esophageal reflux disorder with direct composite veneering aided by a flexible splint matrix

Abstract: Dental erosion is frequently overlooked in clinical practice. The management of erosion-induced damage to the dentition is often delayed, such that extensive occlusal rehabilitation is required. These cases can be diagnosed by a careful clinical examination and a thorough review of the patient's medical history and/or lifestyle habits. This case report presents the diagnosis, categorization, and management of a case of gastro-esophageal reflux disease-induced palatal erosion of the maxillary teeth. The early m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In this study, diclofenac is chosen as an alternative intracanal medicament and its cytotoxic effect tested. Diclofenac sodium, a NSAID [30], is known for its pain reduction on premedication with single dose and post extraction. In this present study, cytotoxicity of diclofenac sodium was tested against L929 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, diclofenac is chosen as an alternative intracanal medicament and its cytotoxic effect tested. Diclofenac sodium, a NSAID [30], is known for its pain reduction on premedication with single dose and post extraction. In this present study, cytotoxicity of diclofenac sodium was tested against L929 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that combination of diclofenac sodium and calcium hydroxide is not deleterious to the surrounding tissues [30,33]. The cytotoxic effect of NSAIDs may be attributed to their ability to inhibit cyclooxygenase pathways mediated by two isoforms COX 1 and COX 2.…”
Section: Discussionmentioning
confidence: 99%
“… 13 14 Although the use of customized transparent polyvinylsiloxane guide or thermoplastic vacuum-formed matrix for constructing the semidirect composite veneers requires minor laboratory procedures and a second dental visit, it is a much easier alternative to free-hand composite build-up, especially when multiple teeth are involved. 15 In this technique, a transparent silicon index is customized for accurate and predictable duplication of a diagnostic wax-up using direct composite restorations without the need for tooth preparation. Both definitive and transitional restorations can be fabricated using this minimally invasive and cost-effective technique.…”
Section: Introductionmentioning
confidence: 99%
“…CAD-CAM materials have been extensively used in restorative dentistry as durable materials to restore teeth with satisfactory mechanical and optical properties [11][12][13][14]. Nevertheless, the frequent exposure of CAD-CAM materials to extrinsic or intrinsic acids might lead to surface deterioration and aws that may eventually doubt the fracture toughness and hence, the durability of the restoration [6,15].…”
Section: Introductionmentioning
confidence: 99%